The time to and type of pancreatic cancer recurrence after surgical resection: is prediction possible? - Kovač, Jelena Djokić; Mayer, Philipp; Hackert, Thilo; Klauß, Miriam (Academic radiology, 2019)
Rationale and Objectives - To evaluate factors predicting pancreatic cancer recurrence, and to determine the most common appearance of tumor relapse. - Materials and Methods - Ninety patients with recurrent pancreatic cancer were retrospectively included in the study. 74.4% had pancreatic head tumors (group 1) and 25.6% pancreatic body and/or tail tumor (group 2). The tumor localization, operative technique, TNM stage, the R-status, tumor grade, lymphovascular, and perineural invasion were recorded. Location of local tumor recurrence, lymph node recurrence, or organ metastases were analyzed on the basis of follow-up CT imaging. - Results - Mean recurrence time was 17.4 ± 13.2 months. The most common recurrence type was local recurrence (84.4%), followed by lymph node (15.5%), liver (14.4%), and lung metastasis (6.7%). The predominant site of local recurrence in pancreatic head tumors was close to superior mesenteric artery, common hepatic artery, and/or celiac artery (57.4%), followed by area defined by portal vein, inferior vena cava, CA or superior mesenteric artery (31.2%). Patients with pancreatic body and/or tail carcinoma had higher incidence (p=0.003) of metastatic disease comparing to pancreatic head tumors, while resection margin was the most common type of local tumor recurrence, seen in 46.7% cases versus 8.2% of patients with pancreatic head tumors (p < 0.001). - Conclusion - The most common recurrence type in patients with resected pancreatic carcinoma was local recurrence along cardinal arteries. The localization of primary tumor influences the type of tumor relapse and site of local recurrence.